HUBUNGAN MODIFIKASI GAYA HIDUP DENGAN KUALITAS HIDUP PASIEN HIPERTENSI : LITERATURE REVIEW - Fachriza Yulia; Wasisto Utomo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Hypertension is a condition in which an increase in blood pressure in the arteries when the heart contracts (systolic) is equal to or above 140 mmHg and blood pressure when relaxing (diastolic) is equal to or above 90 mmHg which causes symptoms such as headaches, visual disturbances, chest pain , shortness of breath, and fatigue. Management of hypertension can be done by way of lifestyle modifications so that it can affect the quality of life of hypertensive patients. This study aims to determine the relationship between lifestyle modification and quality of life of hypertensive patients. Method: This research used a literature review design with searching for research articles using emerald insight, google scholar and pubmed range from 2016-2020. Keywords used for selection article were modification of lifestyle and quality of life of hypertensive patients in the 2016-2020 period. Results: search results for 6 articles that met the inclusion and exclusion criteria based on matrix analysis and based on research objectives, methods, samples, and research results. Literature review shows there is a relationship between lifestyle modification and quality of life in hypertensive patients. Conclusion: Patients with hypertension experience decreased quality of life due to signs and symptoms resulting from hypertension. This will be resolved if hypertensive patients make lifestyle modifications to be healthier such as physical activity, stress management, nutrition, and weight control. Suggestion: Further research is needed to investigate factors that influence lifestyle in hypertensive patients. Keywords: Hypertension; lifestyle modification; quality of life.